Electronic retailers' perception of internet retail service quality / Che Suzana Aida Che Nordin - Che Nordin, Che Suzana Aida (2004)
Dimension of critical factors that impact online retailing (e-quality) are synthesized from literature and organized along eleven e-service quality which are incubative dimension (ease of use, linkage, appearance, structure and layout, content and information) and active dimension (reliability, security, efficiency, communication, support and incentives). Using a random sample of nine Banks that have online banking services, the study benchmark real online transactions against e-quality service dimension. Finding suggests several areas that e-retailers should target for improvement. These areas include enhancing the capabilities of search engine, providing the ability to translate into multiple languages, enhancing way to interact with customer like chatting site, electronic bulletin board, and voice over IP, build more affinity program, reducing the number of clicks to complete a transaction and provide customer the ability to track order status and ease of check out. The use of the Internet as a channel for commerce and information presents an opportunity for business to use the Internet as a tool for customer relationship management (CRM) and electronic customer relationship (ECRM). This study also attempted to uncover the state of customer services and Electronic Customer Relationship Management (E-CRM) implemented in online retailers. It was found that electronic retailers differ in the presence of the 42 different ECRM features and also have different perception of e-service quality.